Review of Tibetan Pastoralists and Development: Negotiating the Future of Grassland Livelihoods edited by Andreas Gruschke and Ingo Breuer - Yonten Nyima (Pastoralism, 2019)
Book details Gruschke A and Breuer I (eds.) Tibetan Pastoralists and Development: Negotiating the Future of Grassland Livelihoods Wiesbaden, Germany Reichert Verlag, 2017 240 pages, ISBN: 9783954902422